Design and implementation of wireless multimedia sensor network node based on DSP and binocular vision - Yun-zhou ZHANG; Pei JIANG; Liang GAO; Li-qiang LI (Tongxin xuebao)
In order to meet the requirement of multimedia information acquisition in wireless sensor network,a new wire-less multimedia sensor node is designed and implemented with the high-performance DSP processor as the core.ZigBee module is used to implement the wireless communication.In virtue of the powerful computing ability and peripheral in-terfaces of DSP processor,the multimedia node owns binocular vision and various sensors such as accelerometer.There-fore,it can attain the real-time perception of environmental information and acquire image/video data.Based on the Zig-Bee protocol,the sensor is able to fulfill short-distance wireless communication and monitoring duty in indoor environ-ment.Experimental results show that the multimedia sensor node designed can accurately obtain and handle the syntheti-cal sensing data in real time.It is suitable for the application of wireless multimedia sensor network.